Emisi Gas Dinitrogen Oksida dari Tanah Sawah Tadah Hujan yang diberi Jerami Padi dan Bahan Penghambat Nitrifikasi - Wihardjaka, A. (JURNAL BIOLOGI INDONESIA, 2010)
ABSTRACTNitrous Oxide Emission from Rainfed Lowland Rice Soils through Applications of Rice Strawand Nitrification Inhibitor Materials. Alternate wet-dry of soil condition under rainfed lowlandsystem influence on source and sink dynamics of green house gases. Lowland rice soil is oneof antropogenic sources of nitrous oxide (N2O) emission produced by microbiologicalnitrification-denitrification mediated processes. Attempt to increase soil productivity in lowlandrice system by organic amendment is predicted to stimulate nitrous oxide production. Theincrease of N2O production in lowland rice could be suppressed by using nitrification inhibitormaterials. A field experiment was conducted in rainfed lowland rice during 2009 dry season. Theobjective was to study interaction of rice straw application and nitrification inhibitor materialson nitrous oxide emission from rainfed lowland rice. Experiment was arranged using factorialrandomizes block design with three replicates and treatment of rice straw application (withoutrice straw, fresh straw, composting straw) and inhibitor nitrification materials (without inhibitornitrification, neemcake, carbofuran). Interaction of rice straw and nitrification inhibitor materialsdecreased significantly N2O emission from lowland rice soil. Nitrous oxide emission in plotwithout rice straw was higher than in plot treated with neither fresh rice straw nor compostingstraw. Application neemcake combined with composting straw emitted lowest nitrous oxidewith flux of 72 g N2O ha-1 season-1, whereas the highest N2O emission was found in plot withoutnitrification inhibitor materials and rice straw with flux of 454 g N2O ha-1 season-1. Comparedwith treatment of without nitrification inhibitor, application of neemcake and carbofuran couldsuppress nitrous oxide emission of 48.6 and 41.3 %, respectively.Key words : nitrous oxide emission, rainfed lowland, rice straw, nitrification inhibitors